(untitled) - Robson, Barry (Amsterdam,New York, 1988)
The desire to understand protein structure has been given new impetus by the explosive growth of biotechnology and the important role of proteins, natural and modified, in this technology. Protein molecules are machines, and protein engineering is opening up a whole new world of machinery on the molecular scale. This work is a simple, but in many ways detailed, introduction, to current knowledge, techniques, and applications
Keywords: Protein engineering,Proteins,Biotechnology,Genetic Intervention,Công nghệ sinh học